Substance abuse and domestic violence within families: a pastoral hermeneutical response - Thesnaar, CH (Nederduitse Gereformeerde Teologiese Tydskrif, 2011)
Substance abuse among young people is an ever increasing reality and one of the most significant contributing factors to domestic violence within families. The essential question is how practical theology and, to be more exact, pastoral interpretive guides (within the local church) can contribute to assist individuals, families and communities in dealing with this traumatic reality in a responsible way. This article argues for a theologically responsible pastoral hermeneutic as it engages with the challenges of the presented case study, within a transdisciplinary approach.